Behaviors of Turkish pregnant women towards gestational diabetes screening - Aydoğmuş, Hüseyin; Aydoğmuş, Serpil; Tıraş, Halil Ibrahim; Cankaya, Zeynep (Pakistan Journal of Medical Sciences, 2021)
Objectives: Although gestational diabetes is the most common metabolic disease in pregnancy some pregnant women still refuse to undergo oral glucose tolerance test (OGTT). The purpose of this study was to evaluate the behavior of pregnant women undergoing OGTT, and to compare perinatal results between women who undergo and refuse OGTT. Methods: This retrospective cohort study was performed by evaluating the data of Izmir Katip Celebi University Gynecology and Obstetrics outpatient clinic between 2012-2017. Data of 2079 pregnant were evaluated retrospectively. Among 373 women who refused OGTT were evaluated as the study group, while remaining 1706 women who underwent OGTT were considered as the control group. The groups were compared with regard to perinatal results. Results: Sixty-two point four percent of the group who refused OGTT had a C-section, while 56.3% of the control group had a C-section (p<0.05). Intrauterine growth retardation, fetal distress, amniotic fluid pathologies, macrosomia, gestational hypertension and perinatal death were slightly higher in pregnant women who did not undergo OGTT compared to the control group, however, the difference was not statistically significant. Conclusion: Maternal complications and poor pregnancy results were found slightly higher in pregnant women who refused OGTT. These results might be explained by assuring glycemic control in pregnant women who refused OGTT by a series of fasting and postprandial blood sugar measurements in our center. doi: https://doi.org/10.12669/pjms.37.5.4176 How to cite this: Aydogmus H, Aydogmus S, Tiras HI, Cankaya Z . Behaviors of Turkish pregnant women towards gestational diabetes screening. Pak J Med Sci. 2021;37(5):1486-1490. doi: https://doi.org/10.12669/pjms.37.5.4176 This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.